How Electronic Word of Mouth and Service Quality Shape Tourists’ Visit Decisions in Agro-Educational Tourism ? - Amri May Maulana Sidik; Evi Lutfia (Vifada Management and Social Sciences, 2024)
Understanding tourists’ visit decisions in the digital era is increasingly important for destination competitiveness, particularly within emerging agro-educational tourism. This study examines the influence of electronic word-of-mouth (e-WOM) and service quality on tourists’ visit decisions at Mabda Islam Agro Edu Park, Indonesia. A quantitative research approach was employed using a survey method, with primary data collected through structured questionnaires distributed to visitors. The study applied a census sampling technique to capture comprehensive visitor perceptions. Data were analyzed using inferential statistical techniques to assess both the individual and joint effects of the proposed variables. The findings indicate that electronic word-of-mouth has a positive and significant influence on tourists’ visit decisions, highlighting the critical role of online information and peer-generated content in shaping travel-related behavior. In addition, service quality was found to positively and significantly affect visit decisions, underscoring the importance of service performance and visitor experience in tourism destinations. The results further confirm that electronic word-of-mouth and service quality simultaneously contribute to tourists’ decision-making processes. This study extends tourism marketing and consumer behavior literature by providing empirical evidence from an agro-educational tourism context in a developing destination. Practically, the findings offer insights for destination managers to strategically manage digital communication and service quality to enhance tourist attraction and sustain competitive advantage.